FACTORS AFFECTING AUDIT FEES IN FINANCIAL SECTOR COMPANIES IN INDONESIA STOCK EXCHANGE - Septiana, Maitri Sutta; Santioso, Linda (International Journal of Application on Economics and Business, 2023)
The purpose of this study is to collect data from empirical studies on the relationship between audit fees and firm size, profitability firm risk, and status of audit firm. 43 companies in the financial sector that have been listed on the Indonesia Stock Exchange for three years, from 2018 to 2020, represent the research sample. Secondary data was used in this study. Panel data regression was chosen as the data analysis model in this study, and EViews 12 SV was used to process the data. The findings of this study indicated that a company's size had a positive effect on audit fees. According to the study's findings, audit fees are not significantly affected by profitability, firm risk, or the status of the audit firm.